WO3 nanocubes for photoelectrochemical water-splitting applications. (November 2019) - Rani, B.Jansi; Kumar, M.Praveen; Ravichandran, S.; Ravi, G.; Ganesh, V.; Guduru, Ramesh K.; Yuvakkumar, R.; Hong, S.I.
Abstract: The photoelectrical splitting of water is an important technique for the efficient generation of hydrogen using catalysts. However, understanding the effects of the size and crystallinity of catalysts is essential for tuning the efficiency of photo electrochemical hydrogen production. In this study, we synthesized WO3 nanocubes with controlled uniform size and shape using a low-temperature hydrothermal method at various temperatures. The nanocubes obtained at a calcinations temperature of 450 °C exhibited higher crystallinity and superior photo catalytic performance during the photo electrochemical production of hydrogen via the oxidation of water in KOH solution. The band gap was determined as ∼2.54 eV with a photocurrent density of 0.0021 mA/cm 2 and a flat band potential around −0.77 V. The nanocubes also exhibited good stability in the alkaline KOH electrolyte for 2 h. Therefore, the superior crystallinity of the WO3 nanocubes could enhance the density of the charge carriers and improve the stability while also decreasing the band gap. These findings may facilitate the fabrication of a stable photo anode for large scale water splitting applications. Highlights: Shape and size controlled WO3 nanocubes synthesized. Physical and photoelectrochemical performance of WO3 nanocubes assessed. Higher photocurrent density of 0.0021 mA/cm 2 achieved with 72% of IPCE. Optimized WO3 nanocubes calcined at 450 °C could be a useful photoanode.